Technopreneurship and Market Feasibility of Modified Carrageenan Hydrogel for Industrial Heavy Metal Remediation - Dulanlebit, Yeanchon Henry; Hernani, Hernani; Liliasari, Liliasari; Amran, Muhammad Bachri; Pangilinan, Greian April (Aptisi Transactions On Technopreneurship (ATT), 2026)
Heavy metal pollution in aquatic systems increases the need for sustainable and efficient natural adsorbent materials, and carrageenan extracted from Eucheuma cottonii, which contains O–H, S=O, C–O–S, and 3,6-anhydrogalactose functional groups, offers strong potential for binding metal ions. However, the adsorption efficiency of natural carrageenan for Copper (Cu2+) and Cadmium (Cd2+) ions remains limited, which frames the central problem of this study. In addressing this issue, the method employed involves synthesizing carrageenan hydrogel through alkaline extraction of Eucheuma cottonii and evaluating its adsorption capacity under controlled experimental conditions. The hydrogel was characterized and tested at pH 6–7, with a contact time of 90 minutes, an initial concentration of 200 mg/L, and an adsorbent mass of 6 g, followed by kinetic and isotherm modeling to analyze adsorption behavior. Based on the Findings, ionic exchange interactions between sulfate ester groups of K-carrageenan and metal cations significantly enhance adsorption performance, with the adsorption process following a pseudo-second-order kinetic model and the Freundlich isotherm providing the best fit R2 > 0.90, indicating heterogeneous multilayer adsorption. In the Conclusion, the chemically modified carrageenan hydrogel demonstrates effective adsorption of copper and cadmium ions and presents strong potential as an eco-friendly and efficient biomaterial for heavy metal remediation.